Efektivitas Penggunaan Media Video Animasi Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPA Kelas VIII SMP Negeri 3 Pariaman (Indo-MathEdu Intellectuals Journal, 2024)
Student learning outcomes are still low, especially in science subject grade VIII at SMP Negeri 3 Pariaman. This is because the media used by teachers in the learning process is still less varied, teachers use media in the form of printed books in which there are pictures that are difficult for students to understand. Therefore, this study aims to determine the effectiveness of the use of animated video media on student learning outcomes in science subject grade VIII at SMP Negeri 3 Pariaman. This type of research is quantitative research with an experimental approach in the form of a quasi experiment. The sample selected was class VIII.3 as a control class with 31 people and class VIII.5 as an experimental class with 31 people. This research was conducted on science subjects with human respiratory system material. The data processing used was a normality test, a homogeneity test, and a hypothesis test using the independent test method of t-test samples, with a significant level of ∝ t table is 2.987 > 2.0003. Which means that H1 is accepted, so that the effective animation video media is significantly applied to the learning outcomes of grade VIII students in science subjects at SMP Negeri 3 Pariaman